Software Engineering Competency Enhancement Program to Support Digital Transformationin the era of Industry 4.0 - ihsan doni irawan; Faisal Yusuf Fadhilah; Zainal Arifin (Community Service Journal : Jurnal Pengabdian Masyarakat Mardira, 2025)
This community service program addresses the low literacy and limited exposure to emerging technologies Cloud Computing, Artificial Intelligence (AI), and the Internet of Things (IoT) among Software Engineering (RPL) students at SMK PGRI Kandanghaur. In response to the competency gap between school curricula and industry demands in the Industrial 4.0 era, the program implements an interactive seminar designed to introduce fundamental concepts, practical applications, and the strategic relevance of these technologies. The activities include expert-led presentations, case-based discussions, and the distribution of digital learning materials to support further independent study. The expected outcomes include improved technological awareness and motivation among students, enhanced readiness for digital transformation, documented seminar outputs, and the publication of community service results. This initiative aims to strengthen students’ foundational competencies and support their alignment with current and future industry requirements.